From Conflict to Catalysis: The Socio-Economic Transformation of Southeast Asia in the Aftermath of World War II - Yap, Chee Kong (Southeast Asia Development Research, 2025)
World War II (WWII) brought devastation in its wake to Southeast Asia (SEA), but it was also the beginning of a profound socio-economic transformation in the region. This review considers how war-time dislocation was a stimulus to post-colonial growth, identifying the long-term structural change initiated after Japanese occupation and the collapse of European imperial powers. The aim of this review is to see how the war enabled the establishment of resilient economies, emerging infrastructure networks, cities, regional clusters, and institutional reform in SEA nations. Through the synthesis of empirical research and historical research, this study examines five general topics: economic restructuring, urbanization, public health reform, political realignment, and regional cooperation. From scholarly literature, the review shows how forced autarky and wartime labour mobilization revealed the weakness of extractive colonial economies and laid the foundation for diversification and export-led industrialization. The article demonstrates how wartime migration and trauma rearranged urban labour markets and public health needs, stimulating long-term investment in social welfare and mental health. It further discusses the influence of nationalist forces, formed amidst resistance to war, on post-war politics and legal modernization. The establishment of ASEAN and mixed legal systems further facilitated the collective trajectory of the region toward stability and integration. This discourse argues that WWII, far from being an era of destruction, was a turning point that shaped the socio-economic trajectories of SEA countries well into the 21st century.